Erythrocyte Profile of Three Spot Gourami (Trichogaster trichopterus PALL) Infected by Digenetic Trematode Parasite (Clinostomum sp.) - Iqbal, Muhammad; Riauwaty, Morina; Syawal, Henni (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2026)
The three spot gourami (Trichogaster trichopterus) is a highly sought-after commodity by the community, often processed into salted fish or consumed fresh.. Clinostomum sp. infection, also known as